Estimates of the impact of COVID-19 on global poverty - Andrew Sumner; Chris Hoy; Eduardo Ortiz-Juarez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In this paper we make estimates of the potential short-term economic impact of COVID-19 on global monetary poverty through contractions in per capita household income or consumption. Our estimates are based on three scenarios: low, medium, and high global contractions of 5, 10, and 20 per cent; we calculate the impact of each of these scenarios on the poverty headcount using the international poverty lines of US1.90, US3.20 and US5.50 per day. Our estimates show that COVID poses a real challenge to the UN Sustainable Development Goal of ending poverty by 2030 because global poverty could increase for the first time since 1990 and, depending on the poverty line, such increase could represent a reversal of approximately a decade in the world's progress in reducing poverty. In some regions the adverse impacts could result in poverty levels similar to those recorded 30 years ago. Under the most extreme scenario of a 20 per cent income or consumption contraction, the number of people living in poverty could increase by 420-580 million, relative to the latest official recorded figures for 2018.
Keywords: I32; 330; global poverty; COVID-19; SDGs; crisis impact